MagooClient 2.1 XML Messaging Client a lean and mean client for XML-based business processes. - Maurer, Paul T. (SOA webservices journal.)
When I first looked over MagooClient from Magoo Software, it was difficult to categorize. I expected that it would be another composite application builder, but that's not what I found. Instead I found a tool that not only allows users to interact with business processes, but that also becomes part of the business process itself. MagooClient can not only reach out and perform Web service requests, but it is designed to also be inserted in the path of XML messages.